2014
DOI: 10.1177/1352458514533844
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cognition, arm function and lower body function after Slow-Release Fampridine treatment

Abstract: SR Fampridine treatment has significant effects on different domains including upper and lower body and cognition. Furthermore, the SSST is more responsive to the effect of SR Fampridine than is the T25FW. ClinicalTrials.gov identifier: NCT01656148.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 38 publications
7
55
0
2
Order By: Relevance
“…(2014) did not improve in their performance in the 9‐HPT following dalfampridine treatment. Other studies, though, have reported improvements in the 9‐HPT in dalfampridine‐treated patients (Allart et al., 2015; Jensen et al., 2014; Lo et al., 2015; Pavsic et al., 2015) while Savin et al. (2016) detected positive effects of dalfampridine treatment only on the dominant hand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2014) did not improve in their performance in the 9‐HPT following dalfampridine treatment. Other studies, though, have reported improvements in the 9‐HPT in dalfampridine‐treated patients (Allart et al., 2015; Jensen et al., 2014; Lo et al., 2015; Pavsic et al., 2015) while Savin et al. (2016) detected positive effects of dalfampridine treatment only on the dominant hand.…”
Section: Discussionmentioning
confidence: 99%
“…In line with a number of previous studies, we did observe a beneficial effect of dalfampridine on the cognitive function of MS patients (Jensen et al., 2014; Ruck et al., 2014; Triche, Ruiz, Olson, & Lo, 2016). In our cohort, the improvement of the performance in the PASAT test was independent of the responder status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 26-28 days of treatment, results showed significant improvements on quantitative tests of upper and lower limb functions as well as the SDMT [50].…”
Section: Symptomatic Drugsmentioning
confidence: 92%
“…All forms of MS were included (relapsing remitting, primary progressive, secondary progressive) [12]. There were wide variations in terms of age, ranging from 18 to 70 years [8,[13][14][15][16] or from 18 to 60 years [17,18].…”
Section: Choice Of Participantsmentioning
confidence: 99%